An Off-Cubes Expanding Approach to the Problem of Separate Determination of the Essential Prime Implicants of the Single-Output Boolean Functions - Basciftci, F.; Kahramanli, S. (EUROCON 2007 - the International Conference on Computer as a Tool, 2007)
The goal of this study is the avoidance of excessive amount of temporary results produced during the minimization process of the two-level single-output Boolean functions of many variables. In this paper we have proposed an off-set based-direct cover minimization method that uses a single on-cube oriented expanding of the off-cubes on which the essential prime implicants are identified in a one by one manner and are used for iterative covering the function being minimized. The amount of temporary results produced by this method does not exceed the size of the offset. The proposed algorithm is up to 3 times faster and uses significantly less amount of memory than well known ESPRESSO.